2009
DOI: 10.1590/s1516-35982009000700025
|View full text |Cite
|
Sign up to set email alerts
|

Características morfométricas e de carcaça de cabritos e cordeiros terminados em confinamento

Abstract: RESUMO -Objetivou-se avaliar o efeito do genótipo sobre as características morfométricas e quantitativas de carcaça de cabritos e cordeiros terminados em confinamento. Foram utilizados 34 animais machos não-castrados (12 cabritos ½ Boer × ½ SRD; 12 cabritos ½ Anglo-Nubiana × ½ SRD; e 10 cordeiros Santa Inês) com peso corporal médio de 18,3 kg e idade média de 135 dias no início do experimento. As médias de altura de cernelha, compacidade corporal e perímetro torácico do genótipo Santa Inês foram superiores às … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
12
0
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 12 publications
6
12
0
7
Order By: Relevance
“…The values for carcass conformation observed in this study corroborated with those reported by Sousa et al (14), where sheep showed better carcass than goats grazing in the Caatinga. Also, Sousa et al (14) reported that sheep had more proportion of meat in the carcass than goats.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The values for carcass conformation observed in this study corroborated with those reported by Sousa et al (14), where sheep showed better carcass than goats grazing in the Caatinga. Also, Sousa et al (14) reported that sheep had more proportion of meat in the carcass than goats.…”
Section: Discussionsupporting
confidence: 92%
“…Also, Sousa et al (14) reported that sheep had more proportion of meat in the carcass than goats. According to Álvarez et al (15), the carcasses with high conformation scores are more valued by consumers, which means better price and appreciation in the market.…”
Section: Discussionmentioning
confidence: 99%
“…Just as the body compact index (kg/cm), measured by the ratio between live weight at slaughter and body length (Sousa et al, 2009), the carcass compact index (CCI) and the leg compact index (LCI) are indicators of a greater or lesser meat production specialization by the genetic groups. In this study the Santa Inês, Brazilian Somali and F1 groups had statistically equal and superior means than the Morada Nova group.…”
Section: Resultsmentioning
confidence: 99%
“…In the sheep meat industry it is favorable to have animals that produce heavy carcasses, with good conformation, high proportion of muscles and adequate amounts of fat (Sousa et al, 2009), but which also present higher yields in prime cuts, hence, a carcass with a higher commercial value (Cezar and Sousa, 2007). Furthermore, it is known that nowadays the demand for quality products is growing and, as described in literature (Bressan et al, 2001;Bonagurio et al, 2003;Pinheiro et al, 2009), meat quality has been examined using pH, color, water holding capacity, cooking losses and tenderness parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Nos sistemas de produção de carne, as características quali-quantitativas da carcaça são importantes, e estão diretamente relacionadas ao produto final, sendo úteis principalmente como parâmetros para que o consumidor possa identificar a qualidade do produto (Sousa et al, 2009). …”
Section: Introductionunclassified